Robson ten groups classification system for caesarean section audit: are our operation theatre registers RTGC enabled? - Abdul Aziz, Fasiha T.; Bhoosreddy, Sushma R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Rising caesarean section rate is a global problem. Robson ten groups classification (RTGC) system of audit has been recommended as the first step towards planning strategies to reduce caesarean section rate. Getting data for this audit is often difficult. If operation theatre (OT) registers are maintained properly this would become easy. The study proposes to know if enough information is available in the operation theatre registers to get caesarean section data for ten groups of Robson classification system. To suggest changes in OT register format for future convenience. Methods: We studied data from 100 consecutive caesarean section entries in OT registers from two medical college institutions to know if the information recorded is adequate to classify these 100 caesarean sections into ten groups given by Robson. Last 100 caesarean section entries into the OT register during the period 1st April 2018 till 31st March 2019 were studied. Results: Presentation of the foetus was the only factor which could be clearly known for all 100 cases. Labour onset whether spontaneous or induced was the least recorded observation in traditional operation theatre registers. The next information which was commonly not recorded was the labour status (woman in labour or not in labour) at the time of caesarean section. Conclusions: For Robson’s classification of caesarean sections to become useful tool to guide strategies in reducing caesarean sections we need to modify format of our OT registers. Traditional OT registers do not provide enough information to categorize caesarean section cases into Robson ten groups. Missing information makes caesarean section audit imperfect or impossible. We suggest a format for it to be incorporated into the operation theatre registers of centres providing maternity services.